(untitled) (Indian Journal of Arid Horticulture, 2025)
Variability studies in bottle gourd indicated that a good amount of genetic variation is present in the evaluated germplasm. Characters like number of fruits/plant, fruit yield/plant, fruit weight and number of seeds/fruit exhibited high estimates of GCV. High estimates of heritability accompanied with high genetic gains observed for number of fruits/plant, fruit yield/plant, fruit weight and fruit length indicated additive type of gene action, hence possibilities for effective improvement by selection for these traits. The characters association studies revealed that number of fruits/plant has strong correlation with yield/plant. On the basis of fruit quality, shape and marketable yield, the line AHLs-11, AHLS-12, AHLS- 24 and AHLS Round-1 were found to be the most potential for exploitation under arid agro-climate.